Factors influencing strategic alliance outcomes in a manufacturing supply chain: Role of alliance motives, interdependence, asset specificity and relational capital - Sambasivan M.; Siew-Phaik L.; Abidin Mohamed Z.; Leong Y.C. (2024)
Indexed by WOS/Scopus